Short-period domain patterning by ion beam irradiation in lithium niobate waveguides produced by soft proton exchange. (February 2023) - Chezganov, D.S.; Vlasov, E.O.; Gimadeeva, L.V.; Neradovskiy, M.M.; Akhmatkhanov, A.R.; Chuvakova, M.A.; Alikin, D.O.; Tronche, H.; Doutre, F.; Baldi, P.; Shur, V.Ya.
Highlights: We propose a focused ion-beam irradiation for periodical poling in lithium niobate waveguides. The ion-beam irradiation is realized after waveguide creation by soft proton exchange method. This method allowed to create the 1-mm-long 2-μm-period domain structure in a channel waveguide. The obtained second harmonic generation efficiency for pulsed 756–378 nm wavelength conversion was up to 6·10 7 % W −1 cm −2 for average power. Abstract: The lithium-niobate-based waveguides have emerged as one of the key platforms for enabling integrated optical technologies. The most common method for creating waveguides in lithium niobate is soft proton exchange (SPE) method. The range of the waveguides applications can be expanded further by creation of near-surface periodical structure of stripe ferroelectric domains within a waveguide (periodical poling) to realize various types of nonlinear optical interactions for creation of frequency conversion devices. However, the joint use of these two procedures (SPE and periodical poling) remains a challenging task. In this paper, we propose a focused ion beam (i-beam) periodical poling technique realized after SPE process for creation of an integrated optical frequency conversion device. The choice of i-beam poling parameters is based on the study of the features of domain structure evolution in lithium niobate after SPE process. We have found that SPE process leads to formation of shallow structure of isolated nanodomains. The revealed isotropic domain growth was caused by the sideways domain wall motion by step generation as a result of merging with these nanodomains. This type of domain kinetics is preferable for periodical poling as it decreases the probability of fast merging of stripe domains due to formation of fast domain walls. Eventually, we have created the 1-mm-long 2-μm-period domain structure in a channel waveguide. The obtained second harmonic generation efficiency for pulse pumping at 756 nm was up to 6·10 7 % W −1 cm −2 for average power and 300 % W −1 cm −2 for peak power indicating the high quality of periodical poling.